Antibacterial activity of cranberry juice concentrate on freshness and sensory quality of ready to eat (RTE) foods. (May 2017) - Harich, Mehdi; Maherani, Behnoush; Salmieri, Stephane; Lacroix, Monique
Abstract: Ready-to-eat (RTE) foods are not further treated before consumption in such a way that may significantly reduce the microbial load, therefore the risk of foodborne disease must be considered. In this regard, the use of natural antimicrobial compounds is an interesting method to be considered. On this topic, the antibacterial activity of cranberry juice concentrate (CJC) have been evaluated in vitro and in situ against 3 foodborne pathogenic bacteria. Results showed a high antimicrobial effect with a noticeable inhibition capacity against Escherichia coli O157:H7, Listeria monocytogenes, Salmonella typhimurium . Acid sensitivity studies of bacteria indicated that at the same pH level (pH = 2.4) in presence of organic acid solution (citric and quinic acids), cranberry juice concentrate showed greater antibacterial effects than the acids due to their phenolic compounds. In situ studies showed 2.5, 1.8 and 5 log reduction of E. coli, L. monocytogenes and S. typhimurium, respectively in presence of cranberry juice concentrate, on pre-cut red peppers after 7 days of storage at 4 °C. A total inhibition of L. monocytogenes on fresh cranberry fruits in primary day of storage, was observed. Cranberries treated with CJC also showed a 3 log reduction of S. typhimurium after 4 days of storage at 4 °C. The results suggest that CJC can be an effective preservation, source of natural antibacterial, to protect the RTE foods from foodborne pathogens contamination without effecting on sensorial properties of treated samples and allow to maintain the freshness, sensory and the nutritional quality of RTE foods. Highlights: Cranberry concentrated juice showed the antibacterial effects on Gram-positive and Gram-negative bacteria. Phenolic compounds present in cranberry juice had important role in antimicrobial activities. Cranberry juice used as a coating did not affect the sensorial properties of red peppers.